2021
DOI: 10.20944/preprints202109.0145.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directed Medical Role Play for Children: Review of the Teddy Bear Hospital Implementations, Objectives, and Reported Experiences

Abstract: Background: Role-playing is often used as a pedagogical method for learning communication in medical education. Therefore, medical play using the Teddy Bear Hospital (TBH) is a concept that can quickly familiarize children with health care and help them develop positive experiences in these areas. This review aims to assess the strengths of TBH, as a form of directed medical role play, in improving health outcomes and well-being in children, along with implanting an awareness of preventive health care in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Adicionalmente, houve melhorias nos conhecimentos sobre cuidados de saúde e relatos de maior felicidade ao consultar um médico após a intervenção. Um estudo realizado com foco na Europa e Ásia, também, deixaram evidente que resultados esmagadoramente positivos, com menores níveis de ansiedade e melhor conhecimento sobre a saúde (JAZRAWY et al, 2021). Com o uso de ressonância magnética, por meio de uma avaliação prospectiva, incluindo crianças e seus pais, o nível de ansiedade das crianças foi significativamente menor, principalmente em meninas, mas inalterado para seus pais (MOREL et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Adicionalmente, houve melhorias nos conhecimentos sobre cuidados de saúde e relatos de maior felicidade ao consultar um médico após a intervenção. Um estudo realizado com foco na Europa e Ásia, também, deixaram evidente que resultados esmagadoramente positivos, com menores níveis de ansiedade e melhor conhecimento sobre a saúde (JAZRAWY et al, 2021). Com o uso de ressonância magnética, por meio de uma avaliação prospectiva, incluindo crianças e seus pais, o nível de ansiedade das crianças foi significativamente menor, principalmente em meninas, mas inalterado para seus pais (MOREL et al, 2019).…”
Section: Resultsunclassified
“…Os achados deste estudo corroboram com estudos anteriores que apontam a eficácia do TBH em diferentes contextos, como evidenciado em pesquisas na Malásia (OTHMAN; TAHAYA, 2013), Europa e Ásia (JAZRAWY et al, 2021). A consistência dos resultados destaca o sucesso da aplicabilidade metodologia.…”
Section: Discussionunclassified
“…The technique adopted was loosely based on the Teddy Bear Hospital (TBH) and the ‘Teddy Bear Therapy’ approach which features in research literature. In work with ill children who need to attend and stay in hospital, the Teddy Bear Hospital (Jazrawy et al, 2021; Moore et al, 2022) involves the use of teddy bears which are ascribed various illnesses and/or in need of various treatments as a means of imparting information to children regarding their illnesses and planned medical interventions in a way that is accessible to them and that also aims to reduce children’s fear and anxiety regarding their situation. Jazrawy et al (2021) in a scoping review that involved 11 studies of the Teddy Bear Hospital (TBH) and medical role plays involving the teddy bears, found that they were overwhelmingly positively received and that children’s level of anxiety was lowered whilst their health knowledge improved.…”
Section: Review Of Literature Regarding the Use Of Teddy Bears In Res...mentioning
confidence: 99%
“…In work with ill children who need to attend and stay in hospital, the Teddy Bear Hospital (Jazrawy et al, 2021; Moore et al, 2022) involves the use of teddy bears which are ascribed various illnesses and/or in need of various treatments as a means of imparting information to children regarding their illnesses and planned medical interventions in a way that is accessible to them and that also aims to reduce children’s fear and anxiety regarding their situation. Jazrawy et al (2021) in a scoping review that involved 11 studies of the Teddy Bear Hospital (TBH) and medical role plays involving the teddy bears, found that they were overwhelmingly positively received and that children’s level of anxiety was lowered whilst their health knowledge improved. In a further review by Moore et al (2022) it was noted that while the Teddy Bear Hospital (TBH) contributed to better communication skills by medical professionals, further training on how to listen (rather than ask questions and/or impart information) was recommended.…”
Section: Review Of Literature Regarding the Use Of Teddy Bears In Res...mentioning
confidence: 99%